Patient-reported outcomes improve with etanercept plus methotrexate in active early rheumatoid arthritis and the improvement is strongly associated with remission: the COMET trial. Issue 01 (16th March 2009) - Kekow, J; Moots, R J; Emery, P; Durez, P; Koenig, A; Singh, A; Pedersen, R; Robertson, D; Freundlich, B; Sato, R
Abstract : Objectives: To compare the effects of etanercept (ETN) 50 mg once weekly plus methotrexate (MTX) versus MTX alone on patient-reported outcomes (PROs) and the relationship between remission and PRO improvement. Methods: In this double-blind, randomised clinical trial (COMET), PROs included: the Health Assessment Questionnaire (HAQ), EuroQoL health status, fatigue and pain visual analogue scales, Hospital Anxiety and Depression Scale, and Medical Outcomes Short-Form-36. Mean changes from baseline were analysed by analysis of covariance using the last observation carried forward method. Results from week 52 are presented. Results: Most PROs demonstrated significantly greater improvements with ETN+MTX than MTX alone, including physical functioning, pain, fatigue and overall health status. A significantly greater improvement in HAQ score was observed in the ETN+MTX than the MTX group (−1.02 vs −0.72; p<0.001) and a greater proportion reached the minimal clinically important difference of 0.22 (88% vs 78%; p<0.006). The relationship between PRO score and clinical status indicated that improvement was greatest among patients achieving remission. Conclusions: Early treatment with ETN+MTX leads to significantly greater improvements in multiple dimensions of PROs than MTX alone. The close relationship between disease activity and PRO improvement suggests that early treatment, with remission as a goal, should maximise the chance of restoring normal functioning and HRQoL.